Cyclin D1 and Its Expression in Neoplastic Gall Bladder Lesions - Agarwal, Anshoo; Singh, Yanina (Med Phoenix, 2020)
Carcinoma of Gall bladder is an infrequent tumour of the gastrointestinal tract and has long been recognized as a highly lethal disease. Tumour markers are glycoprotein that can be determined in blood, saliva, urine and tissues by certain immunological methods. Cyclin D1 is such a marker which is seen to be expressed in various neoplasms. Its role has also been confirmed in gall bladder neoplastic conditions. The onset and progression of gallbladder carcinoma are accompanied with multiple genetic changes that result in qualitative and quantitative alterations in individual gene expression. Immuno-histochemical methods can be used to analyze cyclin D1 levels in gallbladder carcinomas, adenomas and cholecystitis to evaluate their relationships with the pathogenesis, development and metastasis of gallbladder carcinoma.